Reentry : SpaceX, Elon Musk, and the reusable rockets that launched a second space age - Berger, Eric (Science writer) (BenBella Books, Inc., 2024)
"The saga of SpaceX is the story of a diverse cadre of true believers in the limitless potential of space travel. For the first time, Reentry relates the definitive chronicle of how this daring team of risk-takers was able to redefine what it takes to reach the stars"--